2020
DOI: 10.1093/ee/nvaa154
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits of Omnivory for Reproduction and Life History of a Specialized Aphid Predator,Hippodamia convergens(Coleoptera: Coccinellidae)

Abstract: The convergent lady beetle, Hippodamia convergens Guerin-Meneville, is a specialized predator of cereal aphids on the High Plains, completing its first generation each year in winter wheat, the resulting adults dispersing into summer crops and producing additional generations, contingent on the availability of aphids. In the present study, we tested the collective value of supplementary plant resources (sugars, pollen, and seedling wheat leaves), and small amounts of alternative prey, eggs of Ephestia kuehniel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 45 publications
0
10
1
2
Order By: Relevance
“…This fact may be explained by an easier access to food sources (flower pollen and aphids) with lower plant density. Although for lady beetles the main attractant is the presence of aphids, the supplementary plant resources (such as pollen) may be of key significance for reproduction and life history even when suitable prey are not limiting [42]. In our experiment there was no significant effect of thinning on aphids abundance.…”
Section: Mass Of Leavescontrasting
confidence: 53%
“…This fact may be explained by an easier access to food sources (flower pollen and aphids) with lower plant density. Although for lady beetles the main attractant is the presence of aphids, the supplementary plant resources (such as pollen) may be of key significance for reproduction and life history even when suitable prey are not limiting [42]. In our experiment there was no significant effect of thinning on aphids abundance.…”
Section: Mass Of Leavescontrasting
confidence: 53%
“…The omnivorous adult diet resulted in greater female fecundity than did the prey-only diet, supporting our initial hypothesis, and confirming that floral resources complement the nutrition provided by prey, and are essential to maximal reproductive success in this species. Previous studies have similarly concluded that plant-derived foods generally enhance the performance of predatory coccinellids relative to prey-only diets (Lundgren, 2009), including H. convergens (Stowe et al, 2021). Supplemental (plant-derived) foods have long been recognized for their importance to coccinellid survival during periods of prey scarcity (Hodek, 1996;Michaud and Qureshi, 2005), but may also provide phytosterols, key requirements for development and reproduction that insects are unable to synthesize endogenously (Levinson, 1962;Behmer and Nes, 2003;Pilorget et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Supplemental foods of plant origin not only support the survival of predaceous coccinellids in the absence of animal prey (Hodek, 1996;Hatt and Osawa, 2019) they are often necessary for the beetles to achieve maximal fitness (Lundgren, 2009;Michaud, 2018;Stowe et al, 2021). Consequently, these resources are also consumed during periods of prey abundance (Berkvens et al, 2010;Hodek and Evans, 2012;Choate and Lundgren, 2013;Ugine et al, 2019), and may be selectively consumed when particular nutrients are lacking in the diet (Schuldiner-Harpaz and Coll, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This result could reflect reduced egg or sperm viability due to nutrient limitation. Although differences in food quantity or quality do not always affect egg fertility in H. convergens (e.g., Stowe et al, 2021;Vargas et al, 2012a), effects can appear over longer observational periods, as egg fertility declines as a function of maternal age in both very large and very small females, and eggs get progressively smaller with age in the case of the latter (Vargas et al, 2012a(Vargas et al, , 2012b. Any reduction in egg fertility may also improve the survival of siblings, given that cannibalism of infertile eggs within hatching clusters provides a valuable food source for eclosing larvae within hatching clusters (Michaud & Grant, 2004;Osawa, 1992).…”
Section: Discussionmentioning
confidence: 99%